1991
DOI: 10.1164/ajrccm/143.3.522
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen Dioxide Exposure on Pulmonary function and Airway Reactivity in Normal Humans

Abstract: Nitrogen dioxide (NO2) is a product of combustion that has become recognized as a significant component of indoor air in some homes. Despite extensive study, it remains unresolved whether exposures to low levels of NO2 affect airway function or reactivity. These studies were designed to assess effects of various levels and patterns of NO2 exposure on pulmonary function and airway reactivity in normal humans. Normal volunteers screened for the absence of airway hyperreactivity were exposed for 3 h in an environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(57 citation statements)
references
References 9 publications
3
54
0
Order By: Relevance
“…Measured NO 2 and NO concentration values attained peak values of 400 µg m −3 , but the hourly means, which attained a maximum of 189 µg m −3 , never exceeded the hourly European limit for NO 2 . However, these levels could still be dangerous, mostly for firefighters working close to the fire front, because exposure to high NO 2 concentration values harms the lungs and increases respiratory infections (Frampton et al 1991). The explosive hoses placed in plot 515 (Fig.…”
Section: Presentation and Analysis Of Resultsmentioning
confidence: 99%
“…Measured NO 2 and NO concentration values attained peak values of 400 µg m −3 , but the hourly means, which attained a maximum of 189 µg m −3 , never exceeded the hourly European limit for NO 2 . However, these levels could still be dangerous, mostly for firefighters working close to the fire front, because exposure to high NO 2 concentration values harms the lungs and increases respiratory infections (Frampton et al 1991). The explosive hoses placed in plot 515 (Fig.…”
Section: Presentation and Analysis Of Resultsmentioning
confidence: 99%
“…[14][15][16] However, other studies have shown no respiratory effects on asthmatics following exposures to even higher levels. 17,18 Controlled exposures of healthy (non-asthmatic) subjects to NO 2 concentrations above 1,000 ppb for 1 hour or longer indicate increased airway responsiveness; 16,19,20 exposures to lower NO 2 levels have not produced any effects.…”
Section: Introductionmentioning
confidence: 99%
“…29 In another study in humans, alterations of airway reactivity have been reported at exposures as low as 1.5 ppm NO 2 . 30 Potentially toxic NO 2 levels (Ͼ 2 ppm) were observed only during N-IMV using 40 ppm NO. It is very unlikely that many infants would be supported clinically with 40 ppm NO and F IO 2 of 1.0, but nonetheless, this represents a worst case scenario for NO 2 to form during noninvasive support.…”
Section: Discussionmentioning
confidence: 96%